Iconology of Beloved Hand in Flower and Bird Miniature - Muhammad savari (هنرهای زیبا. هنرهای تجسمی)
In Iranian cultural society, the rose and the nightingale symbolize lovers. The rose and bird, or rose and nightingale, are integral to Persian painting, with roots traceable to pre-Islamic times. This combination has been examined as a symbol. The nightingale is considered as a transformation of "Zandav" in Zoroastrian thought, and the rose symbolizes Prophet Muhammad, seen as a transformation of the lotus. The bird, according to mystical texts, represents the soul of the seeker, and the lily symbolizes Anahita in the subconscious of the Iranian artist. In the late Qajar era, special attention was given to painting, particularly the rose and the bird. During the Qajar period, we encounter works where a hand holds a single flower, known as "the beloved's hand." This hand is a distillation of a larger pattern, which this research presents in three hypotheses: the initial pattern is two lovers, seen as a lover giving a flower to the beloved; the second is an angel holding a flower, heralding the birth of Jesus, reflecting a Christian motif in Persian painting; and the third is the offering pattern, where a prince appears to give a flower to an invisible person.By proposing these hypotheses, this research seeks to prove whether "the beloved's hand" can be considered a transformation of the sacrificial pattern as initiation rites. The specific aim of this research was to interpret the meaning of the "beloved's hand" painting. After examining the Painting descriptively and analytically and gathering information from library documents using iconology, the classification and transformation of the motif from the pre-Islamic times to the Qajar period were analyzed. The resulting meanings, in relation to the entire work, indicate the intertwining of the concept of "love" in both pre-Islamic and Islamic periods. This pattern became a political symbol to display the power of rulers across the Islamic world, showcasing their piety and divinity.Previously, in paintings from Bozghalegh, Manichaean princes are depicted holding a flower, seemingly participating in the "Bema" festival. This image aligns with the Iranian tradition of Nowruz, celebrating the spirits of ancient Iranian ancestors at the beginning of spring, symbolizing power and blessing. During the recitation of the Yashts and the "Barsom" ceremony, Iranian kings offered plant sacrifices and made covenants with their deity. The oldest remaining pattern is the marriage ceremony of Tammuz, found in Sumerian myths and Akkadian tablets, where Tammuz marries Inanna. Tammuz, the shepherd god, was associated with spring, plant growth, and the fertility of the land by the people of Mesopotamia. The revival of these patterns in the Qajar period is directly related to the Qajar kings' inclination towards antiquarianism and the influence of Western culture. The Qajar era's fascination with antiquity and Western influences is evident in their art and cultural practices. This period saw a resurgence of ancient motifs and symbols, reinterpreted through the lens of contemporary aesthetics and political needs. The beloved's hand, as a motif, encapsulates this blend of historical reverence and modern reinterpretation.